2008
DOI: 10.1542/peds.2007-0568
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Microchimerism in Underlying Pathogenesis of Biliary Atresia: Quantification and Phenotypes of Maternal Cells in the Liver

Abstract: Significantly more maternal chimeric CD8+ T cells in the livers of patients with biliary atresia suggest that maternal immunologic insults represent the underlying pathogenesis in biliary atresia. The findings support the recently postulated mechanisms of alloautoimmune and/or autoalloimmune responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 21 publications
4
65
1
1
Order By: Relevance
“…Therefore, they hypothesized that tissue-specific microchimeric cells act as target cells that stimulate chronic inflammation. In our series of BA, we have found that the frequency of cells with maternal nuclei was nearly 10-fold greater than that in non-BA controls, 14 and a proportion of XX + CD8 + cells to CD8 + cells in BA is significantly higher than that in controls. Though the threshold for cytotoxic T cell activation is unknown, these maternal cells could theoretically play a role of effector lymphocytes in such a situation as immunologically immature period of fetal life.…”
Section: Ba As An Immune-mediated Disease With Maternal or Transmatermentioning
confidence: 45%
“…Therefore, they hypothesized that tissue-specific microchimeric cells act as target cells that stimulate chronic inflammation. In our series of BA, we have found that the frequency of cells with maternal nuclei was nearly 10-fold greater than that in non-BA controls, 14 and a proportion of XX + CD8 + cells to CD8 + cells in BA is significantly higher than that in controls. Though the threshold for cytotoxic T cell activation is unknown, these maternal cells could theoretically play a role of effector lymphocytes in such a situation as immunologically immature period of fetal life.…”
Section: Ba As An Immune-mediated Disease With Maternal or Transmatermentioning
confidence: 45%
“…[21][22][23] Diagnosis Clinical features: BA may be suspected prenatally, when a cystic structure is observed in the porta hepatis. 24 The classic clinical triad of BA is constituted by (i) jaundice (conjugated, and persisting beyond two weeks of life), (ii) acholic (white) stools, dark urine, and (iii) hepatomegaly.…”
Section: Epidemiologymentioning
confidence: 99%
“…These findings were subsequently confirmed by other authors. 30, 31 Muraji and colleagues 32 in Japan have further characterized these maternal cells as mainly CD8…”
Section: Immunologic Injurymentioning
confidence: 99%